Pengaruh Kualitas Layanan, Promosi dan Digital Marketing Terhadap Keputusan Kredit - Harjum, Harjum; Putra, Pandi; Nisrina, Ulfah Laila (Fakultas Ekonomi dan Bisnis Institut Ilmu Sosial dan Bisnis Andi Sapada, 2023)
The objectives of this study were (1) To determine the quality of service, promotion and digital marketing partially affect credit decisions at PT Mega Finance Parepare Branch. (2) To determine the quality of service, promotion and digital marketing simultaneously affect credit decisions at PT Mega Finance Parepare Branch. The data collection techniques that researchers use in this study are observation, interviews, questionnaires, and documentation. As a population, all credit customers of PT Mega Finance Parepare Branch. In order for this research to be precise and proportional, the slovin formula is used in this study where population members are sampled. Thus the number of samples in this study was 293 people. The results of this study indicate that (1) Service Quality Variable (X1) has a partial effect on credit decisions at PT Mega Finance Parepare Branch with tcount> ttable (3.081> 1.971) and significant <0.05 (0.002 <0.05). (2) Promotion Variable (X2) has no partial effect on credit decisions at PT Mega Finance Parepare Branch with the results of tcount < ttable (1.289 < 1.971) and significant > 0.05 (0.198 > 0.05). (3) Digital Marketing variable (X3) has a partial effect on credit decisions at PT Mega Finance Parepare Branch with tcount < ttable (14.764> 1.971) and significant> 0.05 (0.000 < 0.05). (4) Service Quality, Promotion and Digital Marketing simultaneously affect credit decisions at PT Mega Finance Parepare Branch with Fcount> Ftable (124.475> 2.64) and significant <0.05 (0.000 <0.05). (5) The value of R2 = 0.564 means that the influence of the variables of Service Quality (X1), Promotion (X2) and Digital Marketing (X3) on Credit Decisions (Y) is 56.4%. While the remaining 43.6% is influenced by other variables not included in this study such as product quality, price, brand image, marketing mix, etc.